Characteristics of Oral Adverse Effects following COVID-19 Vaccination and Similarities with Oral Symptoms in COVID-19 Patients: Taste and Saliva Secretory Disorders - Hironori Tsuchiya; Maki Mizogami (Medical Principles and Practice)
Although coronavirus disease 2019 (COVID-19) vaccines exhibit diverse side effects, taste and saliva secretory disorders have remained poorly understood despite their negative impact on the overall quality of life. The present study aimed to characterize oral adverse effects following COVID-19 vaccination and assess their similarities with oral symptoms in COVID-19 patients. A literature search was conducted in databases, including PubMed, LitCovid, and Google Scholar, to retrieve relevant studies. The narrative review indicated that a certain number of vaccinated people develop ageusia, dysgeusia, hypogeusia, xerostomia, and dry mouth, while they are rare compared with COVID-19 oral symptoms. The prevalence of oral adverse effects varies by country/region and such geographical differences may be related to the type of vaccine used. Similar to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, COVID-19 vaccination adversely affects taste perception and salivary secretion in females and older subjects more frequently than in males and younger subjects. Their impairments mostly appear within 3 days of vaccination, and bitter taste is specifically impaired in some cases. Considering that oral adverse effects following COVID-19 vaccination share some characteristics with oral symptoms in COVID-19 patients, it is speculated that the spike protein derived from COVID-19 vaccination and SARS-CoV-2 infection may be pathophysiologically responsible for taste and saliva secretory disorders. This is because such spike protein has the potential to interact with ACE2 expressed on the relevant cells, produce proinflammatory cytokines, and form antiphospholipid antibodies. Our results do not deny the advantages of COVID-19 vaccination, but attention should be paid to post-vaccination oral effects in addition to COVID-19 oral symptoms. Although coronavirus disease 2019 (COVID-19) vaccines exhibit diverse side effects, taste and saliva secretory disorders have remained poorly understood despite their negative impact on the overall quality of life. The present study aimed to characterize oral adverse effects following COVID-19 vaccination and assess their similarities with oral symptoms in COVID-19 patients. A literature search was conducted in databases, including PubMed, LitCovid, and Google Scholar, to retrieve relevant studies. The narrative review indicated that a certain number of vaccinated people develop ageusia, dysgeusia, hypogeusia, xerostomia, and dry mouth, while they are rare compared with COVID-19 oral symptoms. The prevalence of oral adverse effects varies by country/region and such geographical differences may be related to the type of vaccine used. Similar to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, COVID-19 vaccination adversely affects taste perception and salivary secretion in females and older subjects more frequently than in males and younger subjects. Their impairments mostly appear within 3 days of vaccination, and bitter taste is specifically impaired in some cases. Considering that oral adverse effects following COVID-19 vaccination share some characteristics with oral symptoms in COVID-19 patients, it is speculated that the spike protein derived from COVID-19 vaccination and SARS-CoV-2 infection may be pathophysiologically responsible for taste and saliva secretory disorders. This is because such spike protein has the potential to interact with ACE2 expressed on the relevant cells, produce proinflammatory cytokines, and form antiphospholipid antibodies. Our results do not deny the advantages of COVID-19 vaccination, but attention should be paid to post-vaccination oral effects in addition to COVID-19 oral symptoms.